1993
DOI: 10.1016/0887-6177(93)90008-o
|View full text |Cite
|
Sign up to set email alerts
|

The ability of the Dementia Rating Scale to predict everyday functioning

Abstract: The Dementia Rating Scale (DRS) is a brief neuropsychological assessment battery designed to assess five areas of cognitive functioning in the elderly. The relationship between DRS performance and everyday functioning was examined for 50 psychogeriatric patients. Everyday functioning was assessed with a standardized performance measure examining self-care, safety, money management, cooking, medication administration, and community utilization. Regression analyses were conducted for each of the six functional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 0 publications
4
28
1
Order By: Relevance
“…This finding is consistent with several previous studies (Dunn et al, 1990;McCue et al, 1990;Nadler et al, 1993;Richardson et al, 1995). Expressive language (Object Naming) showed the second strongest and only other independent relationship with the IQCODE.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with several previous studies (Dunn et al, 1990;McCue et al, 1990;Nadler et al, 1993;Richardson et al, 1995). Expressive language (Object Naming) showed the second strongest and only other independent relationship with the IQCODE.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have found that measures of executive function are most associated with everyday functioning (Cahn-Weiner et al, 2000;Nadler et al, 1993). The measure of executive functioning used in the current study (Verbal Conceptual Thinking) did not independently predict ratings on the IQCODE.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…It is not clear how the DRS compares in sensitivity to full neuropsychological batteries though this data may be available soon (Mattis, personal communication). Some of its subscales have been shown to be useful in the prediction of activities of daily living (e.g., Nadler et al, 1993). The potential therefore, for the DRS to ultimately be demonstrated to be an efficient clinical tool, providing at least some specification of cognitive functions in patients with dementia, is good.…”
Section: A Brief Review Of Some Current Measures Of Cognitive Functionmentioning
confidence: 98%
“…Regardless of its etiology, executive dysfunction confers significant disability (Nadler et al, 1993;Grigsby et al, 1998). Executive dysfunction is the cognitive impairment most likely to result in impairment of instrumental activities of daily living (IADL) in depressed elderly patients (Kiosses et al, 2001).…”
Section: The Depression-executive Dysfunction Syndrome Of Late Lifementioning
confidence: 99%